CATEGORY OF LYRICISM IN THE PROSE OF I.A. BUNIN (LINGUO-POETHICAL ASPECT) - Luo, Sichen (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article is based on linguistic poetics and devoted to clarifying category of lyricism which forms style of Ivan Alekseyevich Bunin’s prose. In prose of this author appear many features like instance musicality, poetizing of depicted reality, subjectivity, weaken of the narrative, realized by the means of certain phonetic and lexical methods.